KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS CERITA FANTASI SISWA KELAS VII SMP NEGERI 12 PADANG - Nurul Pratiwi Asril; Syahrul Ramadhan (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to determine the correlation between reading comprehension skills and the ability to write fantasy stories among seventh-grade students at SMP Negeri 12 Padang. The research employs a quantitative method with a descriptive correlational approach. The sample consists of 62 students selected using a simple random sampling technique. The research instruments include an objective test to assess reading comprehension skills and a performance test to evaluate students’ ability to write fantasy stories. The results indicate a significant correlation between reading comprehension skills and fantasy story writing skills. The product-moment correlation test shows an r-value of 0.785, meaning there is a positive correlation between the two variables. The findings suggest that the higher a student's reading comprehension skills, the better their ability to write fantasy stories. Thus, enhancing reading comprehension skills can be an effective strategy for improving students’ writing abilities.